Self-reported obstructive sleep apnea is associated with nonresponse to antidepressant pharmacotherapy in late-life depression - Waterman, Lauren (Depress Anxiety, 2016)
BACKGROUND: Obstructive sleep apnea (OSA) is frequently comorbid with late-life depression. The purpose of this project was to determine, using a sample of older adults with major depressive disorder, whether patient-reported diagnosis of OSA was associated with rate of response to venlafaxine. METHODS: Participants from this multisite study were adults ≥60 years old (n = 468) with major depressive disorder and a Montgomery Asberg Depression Rating Scale (MADRS) score of ≥15. Depression response was the outcome variable, defined as a MADRS score of ≤10 for two consecutive assessments at the end of 12 weeks of open-label treatment with venlafaxine 300 mg/day. To assess OSA, participants were asked if they had been diagnosed with OSA using polysomnography. RESULTS: Eighty participants (17.1%) reported a diagnosis of OSA prior to baseline. Participants with OSA were more likely to be male, report greater impairment on measures of health, experience a longer duration of the index episode, and receive an adequate antidepressant trial prior to entering the study. During the 12 weeks of treatment, 40.8% responded to treatment with venlafaxine (43.6%, n = 169/388 of the no OSA group, and 27.5%, n = 22/80 of the OSA group). Participants without OSA were 1.79 times more likely to respond to treatment (HR: 1.79 [95%CI: 1.13–2.86], P < .05) compared to those with OSA. CONCLUSIONS: OSA may impair response to antidepressant pharmacotherapy in depressed older adults. Future studies of antidepressant response rates among depressed older adults with OSA should both prospectively diagnose OSA and monitor adherence to treatments such as continuous positive airway pressure.